A balanced approach to the potential of octopus aquaculture - Ian G. Gleadall; Roger Villanueva; Gregory J. Barord; Zoe Doubleday; Felipe Aguado-Giménez; Nobuhiko Akiyama; Eduardo Almansa; Cheryl L. Ames; Alexander Arkhipkin; Otilio Avendaño; Chris Barrett; Giambattista Bello; et al. (Marine Policy, 2025)

Impacts of spent mushroom substrate amendment and season on microbial communities in a semiarid vineyard soil - José M. Igual; María Soledad Andrades; Cristina Frade; M. José Carpio; Jesús M. Marín-Benito; M. Sonia Rodríguez-Cruz; Angel Valverde (Applied Soil Ecology, 2024)

Microdiverse bacterial clades prevail across Antarctic wetlands - María V. Quiroga; James C. Stegen; Gabriela Mataloni; Don Cowan; Pedro H. Lebre; Angel Valverde (Molecular Ecology, 2024)
Antarctica's extreme environmental conditions impose selection pressures on microbial communities. Indeed, a previous study revealed that bacterial assemblages at the Cierva Point Wetland Complex (CPWC) are shaped by strong homogeneous selection. Yet which bacterial phylogenetic clades are shaped by selection processes and their ecological strategies to thrive in such extreme conditions remain unknown. Here, we applied the phyloscore and feature‐level βNTI indexes coupled with phylofactorization to successfully detect bacterial monophyletic clades subjected to homogeneous (HoS) and heterogenous (HeS) selection. Remarkably, only the HoS clades showed high relative abundance across all samples and signs of putative microdiversity. The majority of the amplicon sequence variants (ASVs) within each HoS clade clustered into a unique 97% sequence similarity operational taxonomic unit (OTU) and inhabited a specific environment (lotic, lentic or terrestrial). Our findings suggest the existence of microdiversification leading to sub‐taxa niche differentiation, with putative distinct ecotypes (consisting of groups of ASVs) adapted to a specific environment. We hypothesize that HoS clades thriving in the CPWC have phylogenetically conserved traits that accelerate their rate of evolution, enabling them to adapt to strong spatio‐temporally variable selection pressures. Variable selection appears to operate within clades to cause very rapid microdiversification without losing key traits that lead to high abundance. Variable and homogeneous selection, therefore, operate simultaneously but on different aspects of organismal ecology. The result is an overall signal of homogeneous selection due to rapid within‐clade microdiversification caused by variable selection. It is unknown whether other systems experience this dynamic, and we encourage future work evaluating the transferability of our results.

The ecological assembly of bacterial communities in Antarctic wetlands varies across levels of phylogenetic resolution - María V. Quiroga; Angel Valverde; Gabriela Mataloni; Valeria Casa; James C. Stegen; Don Cowan (Environmental Microbiology, 2022)
Summary As functional traits are conserved at different phylogenetic depths, the ability to detect community assembly processes can be conditional on the phylogenetic resolution; yet most previous work quantifying their influence has focused on a single level of phylogenetic resolution. Here, we have studied the ecological assembly of bacterial communities from an Antarctic wetland complex, applying null models across different levels of phylogenetic resolution (i.e. clustering ASVs into OTUs with decreasing sequence identity thresholds). We found that the relative influence of the community assembly processes varies with phylogenetic resolution. More specifically, selection processes seem to impose stronger influence at finer (100% sequence similarity ASV) than at coarser (99%–97% sequence similarity OTUs) resolution. We identified environmental features related with the ecological processes and propose a conceptual model for the bacterial community assembly in this Antarctic ecosystem. Briefly, eco‐evolutionary processes appear to be leading to different but very closely related ASVs in lotic, lentic and terrestrial environments. In all, this study shows that assessing community assembly processes at different phylogenetic resolutions is key to improve our understanding of microbial ecology. More importantly, a failure to detect selection processes at coarser phylogenetic resolution does not imply the absence of such processes at finer resolutions.

Correction to: A core of rhizosphere bacterial taxa associates with two of the world’s most isolated plant congeners - Johannes J. Le Roux; Pedro W. Crous; Casper N. Kamutando; David M. Richardson; Dominique Strasberg; Michael J. Wingfield; Mark G. Wright; Angel Valverde (Plant and Soil, 2021)

A core of rhizosphere bacterial taxa associates with two of the world’s most isolated plant congeners - Johannes J. Le Roux; Pedro W. Crous; Casper N. Kamutando; David M. Richardson; Dominique Strasberg; Michael J. Wingfield; Mark G. Wright; Angel Valverde (Plant and Soil, 2021)

Pollution shapes the microbial communities in river water and sediments from the Olifants River catchment, South Africa - Angel Valverde; Errol D. Cason; Alba Gómez-Arias; Derya Bozkale; Danny Govender; Eddie Riddell; Don Cowan (Archives of Microbiology, 2021)

Ecology and biogeochemistry of cyanobacteria in soils, permafrost, aquatic and cryptic polar habitats - Thulani P. Makhalanyane; Angel Valverde; David Velázquez; Eoin Gunnigle; Marc W. Van Goethem; Antonio Quesada; Don A. Cowan (Biodiversity and Conservation, 2015)

Cyanobacteria drive community composition and functionality in rock–soil interface communities - Angel Valverde; Thulani P. Makhalanyane; Mary Seely; Don A. Cowan (Molecular Ecology, 2015)
Most ecological research on hypoliths, significant primary producers in hyperarid deserts, has focused on the diversity of individual groups of microbes (i.e. bacteria). However, microbial communities are inherently complex, and the interactions between cyanobacteria, heterotrophic bacteria, protista and metazoa are likely to be very important for ecosystem functioning. Cyanobacterial and heterotrophic bacterial communities were analysed by pyrosequencing, while metazoan and protistan communities were assessed by T‐RFLP analysis. Microbial functionality was estimated using carbon substrate utilization. Cyanobacterial community composition was significant in shaping community structure and function in hypoliths. Ecological network analysis showed that most significant co‐occurrences were positive, representing potential synergistic interactions. There were several highly interconnected associations (modules), and specific cyanobacteria were important in driving the modular structure of hypolithic networks. Together, our results suggest that hypolithic cyanobacteria have strong effects on higher trophic levels and ecosystem functioning.

Hypolithic and soil microbial community assembly along an aridity gradient in the Namib Desert - Francesca Stomeo; Angel Valverde; Stephen B. Pointing; Christopher P. McKay; Kimberley A. Warren-Rhodes; Marla I. Tuffin; Mary Seely; Don A. Cowan (Extremophiles, 2013)

Biogeography of bacterial communities in hot springs: a focus on the actinobacteria - Angel Valverde; Marla Tuffin; Don A. Cowan (Extremophiles, 2012)

Strains nodulating Lupinus albus on different continents belong to several new chromosomal and symbiotic lineages within Bradyrhizobium - Encarna Velázquez; Angel Valverde; Raúl Rivas; Víctor Gomis; Álvaro Peix; Inne Gantois; José M. Igual; Milagros León-Barrios; Anne Willems; Pedro F. Mateos; Eustoquio Martínez-Molina (Antonie van Leeuwenhoek, 2010)

Differential pathogenicity and genetic diversity among Pectobacterium carotovorum ssp. carotovorum isolates from monocot and dicot hosts support early genomic divergence within this taxon - Moran Yishay; Saul Burdman; Angel Valverde; Tal Luzzatto; Ron Ophir; Iris Yedidia (Environmental Microbiology, 2008)
Summary The capability of Pectobacterium carotovorum isolates to infect monocotyledonous plants has been previously reported; however, no full consideration was given to characterize the association between such isolates and their monocot hosts. To assess differences in aggressiveness among P. carotovorum ssp. carotovorum isolates originating from monocotyledonous or dicotyledonous plants, we used as model plants two susceptible monocot hosts, the ornamentals Zantedeschia aethiopica and Ornithogalum dubium , as well as two common dicot hosts, Solanum tuberosum and Brassica oleracea . Using virulence assays and different genetic analyses we characterized P. carotovorum ssp. carotovorum isolates from diverse geographical locations which originated from plants belonging to four unrelated orders of monocots and five orders of dicots. Invariably, isolates originating from monocots exhibited higher virulence towards the tested monocot plants than dicot isolates, independently of their geographical source. Moreover, monocot and dicot isolates were clearly differentiated by various genetic analyses, such as 16S rRNA sequence clustering, intergenic transcribed spacer‐PCR (ITS‐PCR) banding pattern and amplified fragment length polymorphism (AFLP). We propose that the observed relationship between pathogenicity and genetic diversity among P. carotovorum ssp. carotovorum isolates reveals a co‐evolutionary specialization trend in the interaction between this pathogen and its hosts.

A transgenic tropical maize line generated by the direct transformation of the embryo-scutellum by A. tumefaciens - Angel Valdez-Ortiz; Sergio Medina-Godoy; M. Elena Valverde; Octavio Paredes-López (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)

Differential effects of coinoculations with Pseudomonas jessenii PS06 (a phosphate-solubilizing bacterium) and Mesorhizobium ciceri C-2/2 strains on the growth and seed yield of chickpea under greenhouse and field conditions - Angel Valverde; Araceli Burgos; Tiziana Fiscella; Raúl Rivas; Encarna Velázquez; Claudino Rodríguez-Barrueco; Emilio Cervantes; Manuel Chamber; José-Mariano Igual (Plant and Soil, 2006)

Natural Diversity of Nodular Microsymbionts of Alnus glutinosa in the Tormes River Basin - José M. Igual; Angel Valverde; Encarna Velázquez; Ignacio Santa Regina; Claudino Rodríguez-Barrueco (Plant and Soil, 2006)

Genomic fingerprinting of Frankia strains by PCR-based techniques. Assessment of a primer based on the sequence of 16S rRNA gene of Escherichia coli - José M. Igual; Angel Valverde; Raúl Rivas; Pedro F. Mateos; C. Rodríguez-Barrueco; Eustoquio Martínez-Molina; Emilio Cervantes; Encarna Velázquez (Plant and Soil, 2003)

Upper Oligocene-Lower Miocene shallowing-upwardlacustrine sequences controlled by periodic and non-periodic processes(Ebro Basin, northeastern Spain) - Arantxa Luzón; Angel González; Arsenio Muñoz; Belén Sánchez-Valverde (Journal of Paleolimnology, 2002)